Dorset 83 : Cape Dorset Twenty-fifth Graphics Annual. - Houston, James; Ryan, Patricia (Toronto : Methuen, 1983)
Jamasie ; Kakulu ; Kananginak ; Keeleemeeoomee ; Kenojuak ; Kingmeata ; Lucy ; Mayoreak ; Pitseolak ; Pudlo
boek